The Effect of Misuse of Information Technology and Student Integrity on Academic Fraud Behavior of Students as Prospective Accountants: Pengaruh Penyalahgunaan Teknologi Informasi dan Integritas Mahasiswa Terhadap Perilaku Kecurangan Akademik Mahasiswa Sebagai Calon Akuntan - Novita Maharani; Imelda Dian Rahmawati (Academia Open, 2021)
The purpose of this study was to determine (1) the effect of misuse of information technology on the academic cheating behavior of accounting students as prospective accountants, (2) the effect of student integrity on the academic cheating behavior of accounting students as prospective accountants and (3) the effect of misuse of information technology and student integrity on academic cheating behavior of accounting students as prospective accountants at Muhammadiyah University of Sidoarjo accounting students. In data analysis using tabulation of data obtained from the distribution of questionnaires, from the total number of questionnaires distributed of 100 copies, only 80 were returned and could be processed. The analytical tool used to help manage the data is SPSS software version 18.0. The analytical test used is in the form of normality, validity, and reliability tests. Hypothesis testing was carried out using data analysis tests, namely partial tests and multiple linear regression. The results obtained based on the normality test stated that all data were normal, the results of the validity test of all items in the questionnaire were declared valid because rcount > rtable, all reliability test results were declared reliable. Based on the results of the t test, it can be stated that the misuse of information technology (X1), student integrity (X2), has an effect on (Y) accounting student fraud.